Case Report: Improvement in cognitive functioning following setmelanotide initiation in a patient with Bardet-Biedl syndrome - Kuk, Menjin; Richards, Jesse; Ross, Rachel A. (Frontiers in Endocrinology, 2025)
Bardet-Biedl syndrome (BBS) is a rare genetic condition that results from mutations in a variety of genes crucial for ciliary transport. Consequently, patients with BBS present with a wide array of clinical signs and symptoms that include multiple organ systems. In particular there is a high burden of metabolic disturbances, such as obesity, hyperphagia, and type 2 diabetes, due to the impaired leptin-melanocortin-4 receptor (MC4R) pathway that prevents appropriate activation of MC4R that is normally responsible for signaling hunger and satiety. As such, setmelanotide, an MC4R agonist, has been approved for use to target the obesity and hyperphagia experienced by patients with BBS. Here we report a case of a patient with BBS who was started on setmelanotide for weight management following her BBS diagnosis. One month following treatment initiation, the patient not only endorsed reduced appetite, but also demonstrated a significant improvement in cognitive and affective functioning, as noted in her mental status exam and her performance on the Wechsler Adult Intelligence Scale Fourth Edition (WAIS-IV) tests, when compared to results prior to starting setmelanotide. Although previous studies have reported improved quality of life measures in patients with BBS following setmelanotide initiation, this is the first report of improved cognitive and affective functioning following initiation of the medication, highlighting the need to assess the effects of setmelanotide beyond the metabolic domain in patients with BBS.